Photodynamic Therapy of Cancer: Quality and Prospective of Therapy based on Photosensitizer - Singh, Arun K.; Malviya, Rishabha; Moharana, Ankita; Prajapati, Vedant Kumar; Nirmal, Ashish Kumar (Current Cancer Therapy Reviews, 2023)
To kill cancer cells, photodynamic therapy (PDT) utilizes a light-sensitive medication and light. Light-sensitive drugs are absorbed by cancerous cells. The cells are then illuminated with a specific light or laser by a specialist and oxygen that destroys cancer cells is released. The present study aims to discuss the roles, advancements, and limitations of photodynamic therapy in cancer treatment. Photosensitizers and photosensitizing agents are used in photodynamic treatment to destroy cancer cells. Lasers or other light sources, such as LEDs, may provide illumination. There are reports of a novel nanoplatform for the treatment of HER2-overexpressed breast cancer, as well as other primary and metastatic cancers, using fluorescent electron microscopy PDT/photothermal therapy (PTT) dualtherapy. PDT has a significant benefit over conventional cancer therapies because it may cause fewer adverse effects. PDT-induced immunostimulatory cell death and the production of a robust local inflammatory response might lead to effective local anticancer therapy. PDT has a lower long-term morbidity and recovery time than surgery, chemotherapy, or radiation.
Keywords: photosensitizers